2021
DOI: 10.1108/gm-06-2020-0187
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of subjective career success amongst women employees: moderating role of perceived organizational support and marital status

Abstract: Purpose The purpose of this study is to examine the relationship between subjective career success (SCS) and proactive career behavior as well as family support, with a focus on women professionals in India. The study also investigates the moderating role of perceived organizational support and marital status on these relationships. Design/methodology/approach The sample consists of 363 women professionals working in the information technology-enabled services industry in India. The study is cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…A recent study by Chauhan et al ( 2021 ) revealed that family responsibilities, mentoring and perceived organizational support variables significantly impacted the perceived career success of women; this finding is a wake-up call for women executives to overcome these impediments so as to achieve successful career advancement. Findings from another study showed that perceived organizational support played a positive moderating role in the relationship between proactive career behavior and subjective career success (Agrawal and Singh, 2022 ). Career success is defined as an accomplishment and positive work-related outcome associated with work experiences over time and the corresponding career goal-setting across the lifespan (Gunz and Heslin, 2005 ; Hupkens et al, 2021 ) Much has been written about the definition of career success from two aspects, viz.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Chauhan et al ( 2021 ) revealed that family responsibilities, mentoring and perceived organizational support variables significantly impacted the perceived career success of women; this finding is a wake-up call for women executives to overcome these impediments so as to achieve successful career advancement. Findings from another study showed that perceived organizational support played a positive moderating role in the relationship between proactive career behavior and subjective career success (Agrawal and Singh, 2022 ). Career success is defined as an accomplishment and positive work-related outcome associated with work experiences over time and the corresponding career goal-setting across the lifespan (Gunz and Heslin, 2005 ; Hupkens et al, 2021 ) Much has been written about the definition of career success from two aspects, viz.…”
Section: Introductionmentioning
confidence: 99%
“…The third factor is workplace HR policies which accounts for 9.683% of the variation. The literature also supports the prominent role organisational HR factors as promoters of successful careers of women and enablers of WEE (Desai et al, 2011;Shanmugam and Agarwal, 2019;Mehrajunnisa and Jabeen, 2020;Agrawal and Singh, 2021). A Sub-Saharan African report advocates the need for higher education, additional training and decent maternity leave, among other women-specific business practices in the apparel, mining and mobile telecommunication sectors, to exacerbate the challenges to WEE (Chichester et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“….] an individual's perception of achieving personally meaningful career outcomes" (Agrawal and Singh, 2022).…”
Section: Subjective Career Success (Scs)mentioning
confidence: 99%
“…That is, the employee’s perception of their overall career goals, income aims and their plans for career advancement. SCS is defined as “[…] an individual’s perception of achieving personally meaningful career outcomes” (Agrawal and Singh, 2022).…”
Section: Subjective Career Success (Scs)mentioning
confidence: 99%
See 1 more Smart Citation